Pemanfaatan Google Classroom Sebagai Sarana Belajar dalam Pembelajaran Sejarah (Studi Deskriptif di Kelas XI SMA Pasundan 2 Bandung) - Unengsih, Imas Sri (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
Learning with Google Classroom was chosen by many teachers as a means of distance learning during the Covid-19 pandemic. After Covid-19 was deemed safe, face-to-face learning in the classroom was allowed with the provision that 50% of students could attend school in turn, the rest did online learning. Google classroom is a blended learning platform in education that allows educators to create, share and classify paperless assignments. Google classroom is one of the e-learning applications in history learning. Learning tools that are optimally utilized create effective, efficient learning so that learning objectives can be achieved. History learning is a teaching and learningactivity to obtain a shared picture of important events and the state of past societies. The objectives of this study are (1) To find out the reasons why teachers choose google classroom as a learning tool in learning history; (2) To describe the implementation of history learning with google classroom as a learning tool in class XI Pasundan 2 Bandung High School 2020/2021 Academic Year; (3) To describe the obstacles and efforts of teachers and students in learning history using google classroom. This makes the researcher interested in examining further about google classroom. This research uses a qualitative descriptive study method to get an in-depth description and explanation of the implementation of history learning with google classroom as a learning tool at Pasundan 2 Bandung High School. The results of this study show that (1) The selection of google classroom as a learning tool in learning history was chosen because of its ease and effectiveness in use; (2) History learning with google classroom at Pasundan 2 Bandung High School has not been implemented optimally; (3) Students and teachers are not ready for history learning using google classroom so they experience many technical obstacles.